EPIDEMIOLOGICAL AND THERAPEUTIC ASPECTS OF CRIMEAN-CONGO HEMORRHAGIC FEVER: A REVIEW OF CURRENT DATA - Hamidova Saodat Khikmatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation . This literature review provides a comprehensive analysis of current clinical approaches and therapeutic strategies in the management of Crimean-Congo hemorrhagic fever (CCHF). CCHF is a severe viral zoonotic disease caused by a Nairovirus, transmitted through the bites of infected Hyalomma ticks or contact with infected blood and tissues. The review summarizes the latest findings on epidemiology, clinical manifestations, diagnostic challenges, and treatment protocols. It highlights the disease’s biphasic clinical course, characterized by febrile and hemorrhagic stages, with frequent complications such as hepatic dysfunction, coagulopathy, and multi-organ failure. Therapeutically, the use of ribavirin remains a central but debated intervention, showing the best results when administered early in the disease course. Supportive therapy—including hemodynamic stabilization, electrolyte balance, and transfusion of blood products—is recognized as a critical component of patient management. Recent studies also explore novel antiviral agents such as favipiravir and remdesivir, as well as immunotherapeutic and convalescent plasma approaches. The review concludes that an integrated approach combining early diagnosis, timely antiviral therapy, and intensive supportive care is essential for improving outcomes and reducing mortality in CCHF patients.